Parental satisfaction with the quality of services provided to persons with autism spectrum disorder and their families in Saudi Arabia - Saleh, Salwa R.; Alaoufi, Hiam M.; Eltantawy, Mahmoud Mohamed (Frontiers in Psychiatry, 2024)
The services provided to persons with autism spectrum disorder (ASD) and their families are considered the basic factors that help families meet their needs and those of their children. These services help persons with ASD attain an appropriate level of independence within the society. Therefore, this study aimed to assess the Parents’ satisfaction with the quality of services related to family guidance and education, diagnostic and evaluation services, support and intervention services, and services that aim to improve equal opportunities and life quality among persons with ASD and their parents in Saudi Arabia. This study also aimed to identify the differences in the quality of these services with regard to the age stage of the person with ASD. The study sample consisted of 301 parents of persons with ASD, including 93 fathers and 208 mothers. In this study, a quantitative approach through a questionnaire was used to collect data. Results of this study showed that the parents participating in the study reported the availability of services at an unsatisfactory level with regard to family guidance and education services, support and intervention services, and services that help to improve life quality and equal opportunities. Although the quality of diagnostic and evaluation services was satisfactory, the results indicated no differences in the quality of these services based on the ages of the persons with ASD. The results of this study indicated the importance of developing these services and subjecting them to international quality standards.